IMPLEMENTATION OF SOCIAL MEDIA MARKETING BY CULINARY MSMES - Putri, Intan (Journal of Public Relations and Digital Communication (JPRDC), 2024)
Generally, MSMEs are small-scale businesses owned and managed by individuals or small groups. They typically operate locally and produce a range of products and services, from traditional goods to those using modern technology. MSMEs have unique characteristics, such as flexibility, creativity, and an ability to adapt quickly to changing market demands. This research aims to describe how culinary MSME actors, specifically Sekana Lambidaro in 26 Ilir, Palembang, implement social media marketing. In utilizing social media for marketing, many MSMEs choose to combine various platforms, with Instagram as the primary choice. Instagram attracts MSME entrepreneurs due to its strength in showcasing products through appealing visuals. However, despite Instagram's popularity, only a few MSMEs use marketplaces as their marketing platform. Using social media as a marketing tool is not without challenges. Not all MSME entrepreneurs find it easy to adapt to digital technology. Challenges often stem from internal factors (limited knowledge and skills in information technology) and external factors (hesitance among MSME entrepreneurs to use social media).